Las regulaciones urbanísticas del Gad Cantonal de Riobamba y las Construcciones Informales. - Ríos Chávez, Diego Andrés (2023)
In a broad context of the Latin American cities, particularly in the Ecuadorian ones, the informal settlements are becoming an increasingly prominent issue Individuals with limited financial resources seek housing solutions and often opt to construct and reside in peripherical areas lacking urban planning, essential infrastructure, and basic services. These conditions inevitably result in a diminished quality of life. This stark reality is acutely visible in Riobamba, with a particular focus on its peripheral areas. I observe a high degree of consolidation and unregulated expansion due to the need for more critical infrastructure and essential services. Therefore, the main objective of this research is twofold: first, to propose that the lack of urban regulation within the canton of Riobamba constitutes one of the primary drivers behind the proliferation of informal buildings Secondly, to explore the underlying causes that tolerate this persistent problem. Hence, it is evident that existing regulations must be more adequately aligned with the local context, making it imperative to devise a solution to rectify this situation. In this regard, I propose the implementation of a solution. My research methodology employs a mixed approach, characterized by descriptive and explanatory categories and encompassing the fieldwork bibliographic research, including documentary analysis My studied sample comprises residents living in these informal constructions; it means 196 properties. To gather data, I employed various research techniques and mstruments, including surveys and direct observation, ensuring rigorous data processing within the standards of scientific research. This process enables me to verify my research objectives. The Maicipal Government of Riobamba is responsible for urban development planning and land use regulation. They aim to introduce a fresh and progressive approach to city development that addresses the growth of informal constructions with a less punitive and more conciliatory and facilitative perspective, focusing on legalization and control.